Food Insecurity and Sexual Risk in an HIV Endemic Community in Uganda - Miller, Cari L.; Bangsberg, David R.; Tuller, David M.; Senkungu, Jude; Kawuma, Annet; Frongillo, Edward A.; Weiser, Sheri D. (AIDS and Behavior, 2011)
Food insecurity has been linked to high-risk sexual behavior in sub-Saharan Africa, but there are limited data on these links among people living with HIV/AIDS, and on the mechanisms for how food insecurity predisposes individuals to risky sexual practices. We undertook a series of in-depth open-ended interviews with 41 individuals living with HIV/AIDS to understand the impact of food insecurity on sexual-risk behaviors. Participants were recruited from the Immune Suppression Clinic at the Mbarara University of Science and Technology in Mbarara, Uganda. Interviews were recorded, transcribed verbatim, translated, and coded following the strategy of grounded theory. Four major themes emerged from the interview data: the relationship between food insecurity and transactional sex for women; the impact of a husband’s death from HIV on worsening food insecurity among women and children; the impact of food insecurity on control over condom use, and the relationship between food insecurity and staying in violent/abusive relationships. Food insecurity led to increased sexual vulnerability among women. Women were often compelled to engage in transactional sex or remain in violent or abusive relationships due to their reliance on men in their communities to provide food for themselves and their children. There is an urgent need to prioritize food security programs for women living with HIV/AIDS and address broader gender-based inequities that are propelling women to engage in risky sexual behaviors based on hunger. Such interventions will play an important role in improving the health and well being of people living with HIV/AIDS, and preventing HIV transmission
Keywords: Food insecurity; HIV/AIDS; Uganda; Sexual-risk behavior; Gender; Transactional sex; Violence